Theorizing affective ethnography for organization studies. (November 2019) - Gherardi, Silvia
This article introduces a new label, 'Affective Ethnography', and grounds it within the debates on post-qualitative methodologies and affective methodologies. Affective ethnography is theorized as a style of research practice that acknowledges that all elements—texts, actors, materialities, language, agencies—are already entangled in complex ways, and that they should be read in their intra-actions, through one another, as data in motion/data that move. I discuss three pillars for affective ethnographies that relate to researchers' presence in doing fieldwork and their bodily capacity to affect/be affected. The first is embodiment and embodied knowing. Doing fieldwork implies the ability to resonate with, becoming-with, and the capacity for affective attunement. The second aspect relates to place as flow, and process—to placeness. The third relates to affect as the power to act and therefore to the presence in the fieldwork of the capacity to 'make do', either intentionally or unintentionally.